Low-temperature fracture resistance of plant-mixed heat recycled asphalt mixture based on SCB - Jinrong Wu; Haoran Ren; Aihua Jin (Materials Research Express, 2023)
To investigate the low-temperature crack resistance of plant-mixed heated recycled asphalt mixture, we conducted a semi-circular bending (SCB) test to analyze the effects of the reclaimed asphalt pavement (RAP) content, salt concentration, and loading rate on the crack resistance at −15 °C. The experimental results show that the fracture energy ( G _f ) of the recycled asphalt mixture decreases with an increase in RAP content and salt concentration but increases with an increase in loading rate. When the RAP content is 0%, the Gf of the specimen reaches its maximum value, while when the RAP content is 50%, Gf reaches its minimum value. When the loading rate is 10 mm s ^−1 , the destruction of coarse aggregates in the specimen is much greater than the destruction mode at a loading rate of 2 mm s ^−1 . Meanwhile, as the RAP content increases, the influence of chloride salt on the low-temperature crack resistance of the recycled asphalt mixture fluctuates. According to the quadratic fitting of RAP content and G _f , it can be concluded that a lower loading rate is more helpful in analyzing the degradation mechanism of reclaimed asphalt mixture by salt, and a loading rate of 5 mm s ^−1 ha ^−1 s ^−1 a significant impact on the degradation trend of the recycled asphalt mixture. Finally, by establishing the relationship between the Mohr-Coulomb expression and the ultimate tensile stress, we obtained the cohesive force ( c ) and further analyzed the degradation mechanism of the recycled asphalt mixture under the loading rate and chloride salt. However, the effect of RAP content on c is influenced by various factors, which should be considered comprehensively. These research results enrich the mechanism analysis of the low-temperature cracking performance of plant-mixed heated asphalt mixture and provide theoretical guidance for enhancing the low-temperature cracking resistance design of asphalt pavement.